Design and Fabrication of Local a Solar-Powered device to evaluate of Water Temperature, TDS and pH values in Shatt Al-Arab River - Naeemah Swadi Abdulla ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
In this study, a solar-powered  Water Temperature (WT) , Total Dissolved Solids (TDS) and Hydrogen Ion Concentration (pH) devices was designed, fabricated and tested to evaluate its performance with  measuring  Water Temperature (WT) , Total Dissolved Solids (TDS) and Hydrogen Ion Concentration(pH) values  in the three stations along the Shatt Al-Arab River extended from (Qurna , Ashar and Fao districts)  during  the tidal conditions in Winter 2023.The major components of the design are the Solar Panel cell ,  Solar Charge Controller, Power Solid Battery (GEL) , DC – DC buck converter , WT  ,TDS and pH meters and plastic container. WT, TDS and pH meters which are operated and controlled by buck converter which runs by battery as power source. The results showed that there is an increase in WT at three stations were ranged between (9 - 17 °C). due to the WT which is impacted directly by climate change of the region, The daily fluctuations of TDS and pH of the average spatial values varied from 1237.33 to 214514.66 ppm and 7.96  to  8.04 respectively . the daily fluctuations of pH values in the river was small, while the daily fluctuations of TDS values were showed high in all samples which are exceeding the allowable limit according to (WHO). due to spatial variations in internal environmental conditions. This affirms the impact of sewage water and salinity on the quality of the river water. Thus exceeding the permissible international environmental determinants where river water was  classified as hard water and the intensity of radiation was measured over time during the day during measurement of total melting salts, pH and heat of river water directly for three locations (Qurna, AShar and Fao)